Analysis of the implementation of the pulmonary TB control program at puskesmas Balocci, Balocci district, Pangkep - Rahmadani, Nanang; Hermawan, Adi; Pariati (EcoVision: Journal of Environmental Solutions, 2024)
Tuberculosis is an infectious disease that can cause mortality caused by (Mycobacterium Tuberculosis), it attacks the lung organs and other organs so a TB control program is needed maximally. WHO (World Health Organization) states that TB is a major health problem in the world which causes morbidity in millions of people each year. In 2015-2017 the number of pulmonary TB in the Balocci Health Center was 271 people, of which only 168 patients were declared cured (62.7%), this indicates that the cure rate for Pulmonary TB patients has not reached the set target of 85%. This research was survey research by using a qualitative approach to analyze a control program. This research aims to analyze TB control programs in Balocci Health. The data was collected by observation and in-depth interviews with 6 informants consisting of the head of Mandala Health Center, Tuberculosis staff, tuberculosis patients, patients with pulmonary tuberculosis, and patient Dropouts. The result showed that the TB control program by DOTS strategy in Mandala Health Center was not done well. It is seen that tuberculosis patients don’t get enough knowledge about tuberculosis diseases and understand it, lack of monitoring of the implementation of the Pulmonary TB program for patients with pulmonary tuberculosis which is characterized by a lack of active role in PMO (Drug Controllers) specifically designated for patients with pulmonary TB so that TB patients do not regularly take medication. Based on this research result, Pulmonary TB officers are expected to evaluate the PMO that has been appointed so that the PMO can play an active role in monitoring pulmonary TB patients to take medicine regularly and motivate patients with pulmonary TB.